PENGARUH PAJAK DAERAH DAN DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI DI KOTA BANDAR LAMPUNG TAHUN 2016-2025 - Raditya Aldiansyah; M Ramadhan Caesar; Ica Aprilia Safitri; Juleha Juleha; Nurlaili Nurlaili (JURNAL ILMIAH NUSANTARA, 2026)
Regional economic growth is an important indicator in measuring the success of regional development. One of the factors influencing regional economic growth is the government's ability to manage regional finances, particularly through local tax revenues and balancing funds. This study aims to analyze the effect of local taxes and balancing funds on the economic growth of Bandar Lampung City during the 2016–2025 period. The research employs a quantitative method with a descriptive approach and multiple linear regression analysis. The data used are secondary data obtained from the Central Statistics Agency (BPS), the Directorate General of Fiscal Balance (DJPK), and the financial reports of the Bandar Lampung City Government. The results of the t-test indicate that the local tax variable has a positive and significant effect, while the balancing fund variable has a negative and significant effect on economic growth in Bandar Lampung City. Simultaneously, the local tax and balancing fund variables have a significant effect on the economic growth of Bandar Lampung City.